Genetic Dissection of Adult Plant Resistance to Sharp Eyespot Using an Updated Genetic Map of Niavt14 × Xuzhou25 Winter Wheat Recombinant Inbred Line Population - Liu, Caiyun (Plant disease, 2021)
Wheat sharp eyespot, a disease mainly caused by soilborne fungus Rhizoctonia cerealis, is a threat to world wheat production. Wheat's genetic resistance to sharp eyespot is a potential approach to reducing the application of fungicides and farming practice inputs. To identify the genetic basis of sharp eyespot resistance in Niavt14, a recombinant inbred line population comprising 215 F8 lines from Niavt14 × Xuzhou25, was developed. An earlier linkage map (148 simple sequence repeat markers) was updated with 5,792 polymorphic Affymetrix Axiom 55K single-nucleotide polymorphisms to a new map of 5,684.2 centimorgans with 1,406 nonredundant markers. The new linkage map covered all 21 chromosomes of common wheat and showed a good collinearity with the IWGSC RefSeq v1.0 genome. We conducted quantitative trait locus (QTL) mapping for sharp eyespot resistance using the adult plant response data from the field of five consecutive growing seasons and one greenhouse test. Two stable QTL on chromosomes 2B and 7D that were identified in the previous study were confirmed, and three novel, stable QTL, explaining 4.0 to 17.5% phenotypic variation, were mapped on 1D, 6D, and 7A, which were independent of QTL for phenology and plant height. The QTL on 1D, 2B, 6D, and 7A showed low frequencies in 384 landraces (0 to 10%) and 269 elite cultivars (5 to 23%) from the southern winter wheat region and the Yellow and Huai River Valley facultative wheat region in China, respectively. These identified QTL could be used in wheat breeding programs for improving sharp eyespot resistance through marker-assisted selection